Rancang Bangun Grounding Box Soil Treatment Sebagai Media Pengukuran Resistansi Pentanahan untuk Proteksi Pembangkit Hybrid PV – Angin Politeknik Negeri Malang - Priya Surya Harijanto; Gumilang , Binar Surya; Prasetyo , Budi Eko; Syamsuri , Tresna Umar (Politeknik Negeri Malang, 2024)
This study addresses the issue of high resistance in the grounding system of the Savonius-Solar Hybrid Power Plant at Politeknik Negeri Malang, caused by rocky and sandy soil conditions, with an initial resistance value of 35 Ω. The purpose of this research was to test the effectiveness of soil treatment using bentonite, charcoal, and salt in reducing resistance to meet the PUIL 2011 standard (<5 Ω). This study employed an experimental method with a quantitative approach, measuring resistance values before and after soil treatment application using a three-point earth tester.The results showed that soil treatment successfully reduced the soil resistance from 35 Ω to 2.85 Ω, meeting the maximum standard. This finding indicates that soil treatment is effective in improving the safety and reliability of grounding systems, making it beneficial for application in similar electrical systems located in areas with challenging soil characteristics.